2018
DOI: 10.1002/solr.201800034
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Perovskite Solar Cells with Large Grain‐Size obtained by using the Lewis Acid‐Base Adduct of Thiourea

Abstract: Recently, perovskite solar cells (PSCs) have been rapidly developed, counting as the most promising alternative to the Si solar cells. The fabrication of perovskite films with controlled crystallinity and grain size is critical for highly efficient and stable solar cells. In this work, thiourea (TU) serving as a Lewis acid‐base adduct is introduced into the CH3NH3PbI3 precursor. A smooth and large grained perovskite crystal is obtained without the intermediate phase PbI2 · SC(NH2)2 using the ideal thiourea am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 42 publications
5
91
0
Order By: Relevance
“…[ 132 ] Common S donor Lewis bases mainly include thiophene, thiourea, and their derivatives. [ 86–88,133,134 ] Yang et al introduced derivatives of thiophene IT‐M molecules as Lewis base to successfully passivate the surface defects (the uncoordinated Pb 2+ ) by donating electrons, enhancing the photoluminescence (PL) lifetime to 2.2 μs and further raising the PCE up to 20.5% with a FF as high as 0.81. [ 88 ] Ko et al introduced thiourea as an additive in the MAPbI x Cl 3– x precursor solution to boost the performances and stabilities of fully printable PSCs.…”
Section: Various Types Of Defectsmentioning
confidence: 99%
“…[ 132 ] Common S donor Lewis bases mainly include thiophene, thiourea, and their derivatives. [ 86–88,133,134 ] Yang et al introduced derivatives of thiophene IT‐M molecules as Lewis base to successfully passivate the surface defects (the uncoordinated Pb 2+ ) by donating electrons, enhancing the photoluminescence (PL) lifetime to 2.2 μs and further raising the PCE up to 20.5% with a FF as high as 0.81. [ 88 ] Ko et al introduced thiourea as an additive in the MAPbI x Cl 3– x precursor solution to boost the performances and stabilities of fully printable PSCs.…”
Section: Various Types Of Defectsmentioning
confidence: 99%
“…In recent years, due to the energy crisis and the environmental damage caused by the burning of fossil energy, renewable energy has received more and more attention. [1][2][3][4][5] Due to the power conversion e±ciency (PCE), low preparation cost and high light absorption of hybrid perovskite solar cells (PSCs), it becomes the most promising photovoltaic cells. [6][7][8][9][10][11] The PCE of the PSCs has increased from 3.8% by Miyasaka et al 12 to 23.2% by Jeon et al 13 in just 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Trioctylphosphine oxide (TOPO) and triphenylphosphine oxide (TPPO) were also reported as O‐donor Lewis bases to passivate MHP films effectively, resulting in an extended carrier lifetime of 8 µs and improved PCE (Figure c) . Other Lewis bases such as fullerene, π‐conjugated IDIC and PBDB‐T, non‐fullerene acceptor IT‐M, 2,6‐dimethoxypyridine, caprolactam, thiourea, and fluorine‐containing hydrophobic Lewis acid have also demonstrated success. Recently, Gao et al reported an unencapsulated devices with an active area of 1.0 cm 2 retaining 93% of the original PCE of 17.67% after 2 months under air conditions.…”
Section: Interfacial Modification Layersmentioning
confidence: 99%